Do timeouts matter? A study of euroleague basketball - Carta, G.; Favero, C.; Maver, A. (Journal of Sports Analytics, 2026)
This paper evaluates the effectiveness of timeouts in the EuroLeague using Play-by-Play data to estimate short-run within-game effects and Box-Score data to assess season-level outcomes over the 2021-22 to 2023-24 regular seasons. Within games, timeout effectiveness is identified using an event-study framework comparing team performance in fixed possession windows immediately before and after each timeout, complemented by a difference-in-differences strategy exploiting situations in which teams are unable to call additional timeouts. Performance is measured by the point differential (points scored minus points conceded) over these windows. Under the identifying assumption that pre-timeout trends are comparable across treated and control situations, timeouts are associated with a statistically significant short-run improvement: the average point differential increases from -3.74 before a timeout to -1.20 afterward. Although economically meaningful in reducing opponent scoring runs by approximately 2.5 points on average, the post-timeout differential remains negative, indicating that timeouts primarily stabilize performance rather than reverse game momentum. To assess whether these short-run effects translate into sustained success, we extend the standard Four-Factor Model of Wins with a fifth factor capturing team-level timeout effectiveness. This additional factor provides no incremental explanatory power. From a coaching perspective, timeouts appear to function as short-term damage-control devices but do not systematically affect season-long competitive outcomes.